Effect of coupled temperature-humidity drying on multi-scale structure and in vitro digestibility of corn resistant starch - Qing Su; Lirong Chen; Linlin Sun; Xingya Wang; Yuqiu Guo; Meimei Zhao; Kaichang Liu; Kuijie Gong (Food Chemistry, 2026)

An accelerated XFEM framework for fatigue crack propagation analysis of shield tunnel linings subjected to cyclic train loads - Wenbo Yang; Zhenian Wang; Linlin Yang; Ziyuan Su; Yang Zhou; Chaofan Yao; Fangyin Wu (Computers and Geotechnics, 2026)

Performance and wastewater treatment efficiency of artificially prepared aerobic granular sludge - Xuanzhe Yan; Jinlong Wang; Kailong Liu; Hao Wu; Wei He; Yongmei Zhang; Linlin Tong; Su Li; Zhaoyang You (Biodegradation, 2026)

Prescription principle, phytochemistry, pharmacological activities and clinical applications of Huangqin decoction: a comprehensive review - Yan Fang; Haizhen Liang; Linlin Lu; Xijie Tian; Yuting Zhang; Junyu Zhang; Zhifeng Dai; Xiaojuan Chen; Juan Song; Tao Su; Zhongqiu Liu; Baiping Ma (Phytochemistry Reviews, 2026)

Spatial heterogeneity of wildfires in Southern China during the Last Glacial Maximum - Binxu Liu; Jia Liu; Xingyuan Qin; Linlin Chen; Jiaxi Zhou; Zhiyun Lu; Robert A. Spicer; Shufeng Li; Tao Su (Global and Planetary Change, 2026)

NCAPG reprograms glycolytic and lipid metabolism by sustaining glycerophospholipid flux in small-cell lung cancer - Yang Sun; Jinglin Wen; Rui Su; Linlin Liu (Molecular and Cellular Biochemistry, 2026)

Mechanistic study of wheat straw-enhanced sulfur release and denitrification in a pyrite-based bioretention system: Iron–sulfur–carbon synergistic interactions - Zhaoyang You; Jinlong Wang; Tao Wang; Xi Chen; Yongmei Zhang; Su Li; Linlin Tong; Kinjal J. Shah (Chemosphere, 2026)

The “Last-mile Efforts” of Subseasonal Prediction and Services for Climate Resilience and Sustainability: Review and Outlook - Jing Yang; Mengqian Lu; Anling Liu; Tat Fan Cheng; Yuxian Pan; Miaoni Gao; Lun Dai; Shentong Li; Wen Deng; Xinyao Feng; Shiyu Zhang; Lu Tang; et al. (Advances in Atmospheric Sciences, 2026)
Subseasonal predictions from 2 weeks to 2 months have made significant advancements over the past decade, driven by progress in physical understanding, climate modeling, computational capabilities, and artificial intelligence (AI). These predictions are increasingly in demand due to their potential to provide stakeholders with adequate lead time for effective disaster adaptation, mitigation, and resource management. However, there remain critical gaps in the engagement between prediction providers and service users. Providers often lack insight into the specific needs of users and do not have transferrable strategies to build trust through tailored evaluations and clear confidence levels, which often results in repeatedly devising approaches for each provider–user interaction. Further, users frequently struggle to interpret predictions and are hesitant to make decisions based on these uncertain outcomes. This paper attempts to make “last-mile efforts” by reviewing relevant literature, operational systems, and the most informative communications and engagement strategies with key sectors. It proposes a preliminary framework to standardize the approach for provider–user interaction in the context of subseasonal prediction and services, with potential applicability and extension to seamless prediction systems in the future. Lastly, we underscore future directions for subseasonal predictions, emphasizing the integration of dynamic climate modeling and AI-driven enhancements with large ensemble techniques to improve both reliability and confidence. This review is part of the United Nations Educational Scientific and Cultural Organization (UNESCO) International Decade of Sciences for Sustainable Development (2024–33) and contributes to the Seamless Prediction and Services for Sustainable Natural and Built Environment (SEPRESS) Program (2025–32), an initiative endorsed under this global framework.

Corrigendum to “China's agricultural upgrade: Digital inclusive finance driving high-quality development” [J. Rural Stud., Volume 121 (2026), 103927] - Liangen Zeng; Yuandong Zou; Yisha Fu; Yanfeng Jiang; Xiaoyan Zhang; Linlin Dai; Yiqing Su (Journal of Rural Studies, 2026)

Tailoring monoglyceride oleogel crystallization by eutectic and crystal nucleation disturbance: functional frozen specialty fat for use in croissants - Yanxia An; Yi Han; Ziwei Liu; Jingyuan Su; Jian Zhang; Keke Liu; Linlin Li (Food Research International, 2026)

Oleogels in flour-based foods: an overview from the perspective of crystalline structure and functional performance - Yi Han; Linlin Li; Lukai Ma; Jingyuan Su; Yang Zhao; Jian Zhang; Yanxia An (Food Chemistry, 2026)

Corrigendum to “China's agricultural upgrade: Digital inclusive finance driving high-quality development” [J. Rural Stud., Volume 121 (2026), 103927] - Liangen Zeng; Yuandong Zou; Yisha Fu; Yanfeng Jiang; Xiaoyan Zhang; Linlin Dai; Yiqing Su (Journal of Rural Studies, 2026)

A novel bacteriophage pAEh1 for controlling Aeromonas hydrophila infection in aquaculture - Sifan Jiang; Boyang Zhou; Tongping Zhang; Rongsi Dai; Su Long; Linlin Yang; Mingwang He; YanJiao Fu; Jiajing Guo; Zhipeng Gao (Fish & Shellfish Immunology, 2026)

China's agricultural upgrade: Digital inclusive finance driving high-quality development - Liangen Zeng; Yuangdong Zou; Yisha Fu; Yangfeng Jiang; Xiaoyan Zhang; Linlin Dai; Yiqing Su (Journal of Rural Studies, 2026)

Ultrasensitive, signal-complementary piezo-capacitive pressure sensor for complex physiological monitoring and HMI - Daojian Su; Linlin Jiang; Zijun Pan; Changhong Yang; Chang Liu; Rongxiao Liu; Tong Liu; Xin He; Shifeng Huang; Zhenxiang Cheng (Chemical Engineering Journal, 2025)

Microwave-assisted modification for enhancing the slow-release performance of biochar-based fertilizer and application - Linlin Zhu; Bingzhe Su; Chen Guan; Yao Chen; Dongye Huang; Jiayao Zhou; Qiuyu Chen; Xiaochen Liu; Fei Tian; Zhansheng Wu (Journal of Soils and Sediments, 2025)

Alginate-polylysine-alginate (APA) microencapsulated transgenic human amniotic epithelial cells ameliorate fibrosis in hypertrophic scars - Linlin Su; Yanhui Jia; Yan Li; Jihong Shi (Inflammation Research, 2025)

MitoQ reducing sevoflurane-induced cognitive dysfunction by modulating mitochondrial dysfunction - Hengjie Su; Zhibin He; Haotian Wu; Linlin Wang; Huan Zhang; Siyi Yan (Metabolic Brain Disease, 2025)

Temporin-GHaR Peptide Alleviates LPS-Induced Cognitive Impairment and Microglial Activation by Modulating Endoplasmic Reticulum Stress - Da-Qi Zhang; Xiaoqian Dong; Simin Su; Linlin Zhang; Jiayu Zhang; Wenjing Yang; Wenting Hu; Lushuang Li; Yanting Song; Xi Xie; Qifu Li; Rong Wang; et al. (Probiotics and Antimicrobial Proteins, 2025)

Social and ecological factors on the perception of cultural ecosystem services and disservices: Insights from Shanghai, China - Rongfei Su; Shiyu Ye; Linlin Yu; Jingbin Wu; Yan Kang; Ruishan Chen (Landscape and Urban Planning, 2025)

Construction of Fenton-like systems based on hierarchical nanoconfinement for efficient antibiotic removal - Linlin Su; Wei Hu; Xiaolun He; Chao Chen; Min Xu; Xiaoyu Yu; Yan Liu; Gang Yang; Lulu Long (Journal of Environmental Chemical Engineering, 2025)

Enhanced viability of Lactiplantibacillus plantarun by encapsulation with whey protein isolate fibrils and polysaccharides through layer-by-layer coating - Siyuan Li; Wei Su; Yu Zhang; Wanling Gan; Xiaoli Liu; Linlin Fan (Food Hydrocolloids, 2025)

Climate evolution and its driving factors in the Tethys Sea region during the Cenozoic - Jiangbo Meng; Jiagang Zhao; Linlin Chen; Paul J. Valdes; Alex Farnsworth; Svetlana Popova; Mine Sezgül Kayseri-Özer; Gaurav Srivastava; Jian Huang; Tao Su; Zhekun Zhou; Shufeng Li (Science China Earth Sciences, 2025)

The influence of different drying methods on the molecular structure and digestive resistance of type 3 resistant starch (RS3) - Qing Su; Linlin Sun; Lirong Chen; Xingya Wang; Kaichang Liu; Kuijie Gong (Food Chemistry, 2025)

Development and validation of a prediction model for the depressive symptom risk in commercial airline pilots - Jie Zhang; Xuhua Chen; Lin Zhang; Haodong Qi; Erliang Zhang; Minzhi Chen; Yiran Wang; Yunfei Li; Yan Chen; Qingqing Duan; Feng Shi; Linlin Wang; et al. (EPMA Journal, 2025)

Exosomal miR-27a-5p attenuates inflammation through Toll-like receptor 7 in foodborne Salmonella infections - Mingjuan Qu; Shengfa Su; Linlin Jiang; Xin Yu; Jianlong Zhang; Hongwei Zhu; Kexue Han; Xingxiao Zhang (Veterinary Microbiology, 2025)

Hydrogen gas enhances Arabidopsis salt tolerance by modulating hydrogen peroxide-mediated redox and ion homeostasis - Linlin Xiao; Yueran Hu; Yiting Wang; Chengsi Lv; Na Zhan; Hongying Duan; Jiuchang Su (Plant Science, 2025)

Metagenomics and metaproteomics reveal the effects of sludge types and inoculation modes on N,N-dimethylformamide degradation pathways and the microbial community involved - Yunchuan Xian; Linlin Cao; Yuxiang Lu; Qiuhong Li; Chengyuan Su; Yuan He; Guangrong Zhou; Shenglong Chen; Shu Gao (Journal of Hazardous Materials, 2025)

Enhanced peracetic acid activation under Far-UVC Radiation: Micropollutant degradation and radical assessment - Tao Yang; Maoju Jiang; Peng Su; Qixiao Lv; Wenqi Li; Chenlong Liu; Bin Zhang; Haochen Zhang; Linlin Zang; Minchao Liu; Jun Ma (Chemical Engineering Journal, 2024)

The casein in sheep milk processed by cold plasma technology: Phosphorylation degree, functional properties, oxidation characteristics, and structure - Jiaying Zhang; Jiaqing Song; Shuangshuang Wang; Yangyu Su; Linlin Wang; Wupeng Ge (Food Chemistry, 2024)

Ultrasensitive monitoring of PCB77 in environmental samples using a visible-driven photoelectrochemical sensing platform coupling with exonuclease I assisted in target recycling - Lining Su; Guizhen Wang; Linlin Zhao; Yuan Deng; Yujing Guo; Yong Xiao; Huanwen Wang; Chuan Dong; Lifang Fan (Science of The Total Environment, 2024)

Investigation on the exopolysaccharide production from blueberry juice fermented with lactic acid bacteria: Optimization, fermentation characteristics and Vis-NIR spectral model - Suqun Yang; Yang Tao; Xiayidan Maimaiti; Wei Su; Xiaoli Liu; Jianzhong Zhou; Linlin Fan (Food Chemistry, 2024)

Constructing efficient lithium salt dissociation solid-state electrolytes with high conductivity and transference number of Li ions for stable all-solid-state lithium batteries - Zengcai Guo; Shimin Liao; Feng Li; Linlin Shi; Bihai Su; Jingbo Mu; Yanming Wang; Zhongkai Huang; Feng Xu; Chaowen Guan (Chemical Engineering Journal, 2024)

A comprehensive “quality-quantity-activity” approach based on portable near-infrared spectrometer and membership function analysis to systematically evaluate spice quality: Cinnamomum cassia as an example - Ziwei Zou; Bingjian Guo; Yue Guo; Xiaolong Ma; Sanshan Luo; Linlin Feng; Ziping Pan; Lijun Deng; Shihan Pan; Jinbin Wei; Zhiheng Su (Food Chemistry, 2024)

Impact analysis of hydraulic residence time and dissolved oxygen on performance efficiency and microbial community in N, N-dimethylformamide wastewater treated by an AnSBR-ASBR - Yuchen Wang; Linlin Cao; Yiying Lu; Junjie Liao; Yuxiang Lu; Chengyuan Su; Shu Gao (Environmental Pollution, 2024)

How the subsurface wastewater infiltration systems with iron‑carbon micro-electrolytic substrate achieve high pollutants removal: A metabolomic view - Yinghua Li; Linlin Peng; Yiyan Wang; Yue Zhang; Fei Su; Jie Qian (Journal of Water Process Engineering, 2024)

Angiotensin II type 2 receptor agonist attenuates LPS-induced acute lung injury through modulating THP-1-derived macrophage reprogramming - Liangzhi Chen; Ping Gong; Yue Su; Linlin Meng; Muyun Wang; Wei Gao; Qinghua Liu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Grey matter structural alterations in anxiety disorders: a voxel-based meta-analysis - Han Liu; Zeqi Hao; Shasha Qiu; Qianqian Wang; Linlin Zhan; Lina Huang; Youbin Shao; Qing Wang; Chang Su; Yikang Cao; Jiawei Sun; Chunjie Wang; et al. (Brain Imaging and Behavior, 2023)

Depth investigation of the regulation mechanism of SiO2 on the denitrification performance and sulfur resistance of MnCe/Ti SCR catalyst - Mengxia Qing; Linlin Zhang; Liang Liu; Yaxin Chen; Yunda Su; Sheng Su; Song Hu; Yi Wang; Jun Xiang (Chemical Engineering Journal, 2023)

Mechanism of adsorption of hazardous gases by MoTe2 monolayers modified with nanoclusters - Zhiyan Feng; Long Lin; Linlin Su; Donglin Pang; Pei Shi (Journal of Environmental Chemical Engineering, 2023)

Molecular mechanisms affecting the stability of high internal phase emulsions of zein-soy isoflavone complexes fabricated with ultrasound-assisted dynamic high-pressure microfluidization - Junrong Huang; Xutao Chen; Danxia Su; Linlin Chen; Caidi Chen; Bei Jin (Food Research International, 2023)

Hair Selenium of Residents in Keshan Disease Endemic and Non-endemic Regions in China - Yuehui Jia; Ruixiang Wang; Guijin Li; Chen Feng; Lei Qi; Yuanyuan Wang; Shengqi Su; Yuanjie Zou; Xu Liu; Yanan Wang; Yiyi Zhang; Linlin Du; et al. (Biological Trace Element Research, 2023)

Long-term performance study applying a tandem AnSBR-ASBR to treat wastewater containing N, N-dimethylformamide: Sludge physicochemical properties, microecology, and functional genes - Linlin Cao; Chengyuan Su; Yiying Lu; Jinyan Wu; Lixin Wei; Junjie Liao; Yunchuan Xian; Shu Gao (Journal of Environmental Chemical Engineering, 2023)

Development of SSR markers on the basis of the Panax notoginseng transcriptome for agronomic and biochemical trait association analyses - Linlin Su; Yingpeng Zhang; Ye Yang; Yuan Qu; Xiuming Cui; Feng Ge; Diqiu Liu (Journal of Applied Research on Medicinal and Aromatic Plants, 2023)

Use of iron-loaded biochar to alleviate anammox performance inhibition under PFOA stress conditions: Integrated analysis of sludge characteristics and metagenomics - Linqin Tang; Chengyuan Su; Qing Wang; Linlin Cao; Yunchuan Xian; Shitong Wen; Yijie Zhou; Shu Gao (Science of The Total Environment, 2023)

A High Concentration of Polycyclic Aromatic Hydrocarbons in Umbilical Cord Tissue is Associated with an Increased Risk for Fetal Neural Tube Defects - Shengju Yin; Ying Sun; Jinhui Yu; Zaiming Su; Mingkun Tong; Yali Zhang; Jufen Liu; Linlin Wang; Zhiwen Li; Aiguo Ren; Lei Jin (Exposure and Health, 2023)

Impact of diurnal temperature range on other infectious diarrhea in Tongcheng, China, 2010–2019: a distributed lag non-linear analysis - Linlin Wang; Jian Cheng; Guanghui Yu; Qiqun Zong; Chunxia Zhai; Wanqin Hu; Yuhua Wang; Ziye Yan; Tingyu Zhang; Junwu Wang; Chengye Zhang; Hong Su; et al. (Environmental Science and Pollution Research, 2023)

Metagenomic and extracellular polymeric substances analysis reveals the mechanism of exogenous N-hexanoyl-L-homoserine lactone in alleviating the inhibition of perfluorooctanoic acid on anammox process - Linqin Tang; Chengyuan Su; Cuiping Fan; Linlin Cao; Zhu Liang; Yufeng Xu; Zhengpeng Chen; Qing Wang; Menglin Chen (Bioresource Technology, 2023)

Cenozoic plants from Tibet: An extraordinary decade of discovery, understanding and implications - Zhekun Zhou; Jia Liu; Linlin Chen; Robert A. Spicer; Shufeng Li; Jian Huang; Shitao Zhang; Yongjiang Huang; Linbo Jia; Jinjin Hu; Tao Su (Science China Earth Sciences, 2023)

Current recycling strategies and high-value utilization of waste cotton - Linlin Lu; Wei Fan; Xue Meng; Lili Xue; Shengbo Ge; Chen Wang; Shin Ying Foong; Cindy S.Y. Tan; Christian Sonne; Mortaza Aghbashlo; Meisam Tabatabaei; Su Shiung Lam (Science of The Total Environment, 2023)

The Paleogene to Neogene climate evolution and driving factors on the Qinghai-Tibetan Plateau - Jiagang Zhao; Shufeng Li; Alexander Farnsworth; Paul J. Valdes; Tammo Reichgelt; Linlin Chen; Zhekun Zhou; Tao Su (Science China Earth Sciences, 2022)

Late Eocene sclerophyllous oak from Markam Basin, Tibet, and its biogeographic implications - Linlin Chen; Weiyudong Deng; Tao Su; Shufeng Li; Zhekun Zhou (Science China Earth Sciences, 2021)

Characteristics of Plastic Pollution in the Environment: A Review - Penghui Li; Xiaodan Wang; Min Su; Xiaoyan Zou; Linlin Duan; Hongwu Zhang (Bulletin of Environmental Contamination and Toxicology, 2021)

High-frequency in vitro plantlet regeneration in Lilium davidii var. unicolour Salisb, an important edible and medicinal plant, and confirmation of genetic fidelity of regeneration plantlets using ISSR markers - Linlin Yang; Liqin Chao; Xiuhong Su; Chunyan Wang; Chengming Dong; Suiqing Chen (Plant Biotechnology Reports, 2021)

Multi‐century drought variability in the southern Min Mountains - Xiaoya Yan; Yang Deng; Haowen Fan; Jiajia Su; Linlin Gao; Xiaohua Gou (International Journal of Climatology, 2020)
Information on moisture variability is important for climate adaptation and planning, which is urgently needed for the Jiuzhaigou County after it was hit by a magnitude 7.0 earthquake in August 2017, resulting in potential interactions between the earth surface processes and the hydroclimate. To study the regional hydroclimatic history beyond instrumental records, the first tree‐ring hydroclimate reconstruction, based on Pinus tabuliformis , was conducted in the southern Min Mountains, which is situated close to the areas affected by the Jiuzhaigou earthquake. The reconstruction, spanning from 1684 to 2017, explained 59% of the variance for May–August standardized precipitation evapotranspiration index at a 12‐month scale during 1962–2017. The recent drought, which occurred from 1992 to 2017 was the longest in duration, largest in magnitude, and had the second highest intensity. The most severe single year drought occurred in 1824, which was lower than the long‐term mean by 4 σ and affected several regions in and around the Northeast Qinghai‐Tibet Plateau. The drought reconstruction was consistent with other moisture reconstructions, but dissimilar were also exist during some periods. There was a significant correlation between drought reconstruction and sea surface temperature over many oceans. However, the correlations were unstable over time. This study suggests the importance of developing a density tree‐ring network to identify the spatial and temporal drought variability, as well as long‐term record for understanding regional climate dynamics.

Effect of polysaccharides extracted from Sipunculus nudus (SNP) on the lifespan and immune damage repair of Drosophila melanogaster exposed to Cd (VI) - Jie Su; Linlin Jiang; Jingna Wu; Zhiyu Liu; Yuping Wu (Natural Product Research, 2018)

MicroRNA-192 regulates hypertrophic scar fibrosis by targeting SIP1 - Yan Li; Julei Zhang; Wei Zhang; Yang Liu; Yuehua Li; Kejia Wang; Yijie Zhang; Chen Yang; Xiaoqiang Li; Jihong Shi; Linlin Su; Dahai Hu (Journal of Molecular Histology, 2017)

miR-155 promotes cutaneous wound healing through enhanced keratinocytes migration by MMP-2 - Longlong Yang; Zhao Zheng; Qin Zhou; Xiaozhi Bai; Lei Fan; Chen Yang; Linlin Su; Dahai Hu (Journal of Molecular Histology, 2017)

Exosomes derived from human amniotic epithelial cells accelerate wound healing and inhibit scar formation - Bin Zhao; Yijie Zhang; Shichao Han; Wei Zhang; Qin Zhou; Hao Guan; Jiaqi Liu; Jihong Shi; Linlin Su; Dahai Hu (Journal of Molecular Histology, 2017)

A novel short anionic antibacterial peptide isolated from the skin of Xenopus laevis with broad antibacterial activity and inhibitory activity against breast cancer cell - Siming Li; Linlin Hao; Wanguo Bao; Ping Zhang; Dan Su; Yunyun Cheng; Linyan Nie; Gang Wang; Feng Hou; Yang Yang (Archives of Microbiology, 2016)

CspE is Overproduced by Temperature Downshift in the Acinetobacter johnsonii DBP-3 - Dan Su; Linlin Hao; Fuwang Chen; Siming Li; Ahmed Mohamed Abdelrahman; Yu Zhang; Hao Yu; Songcai Liu; Mingtang Li (Current Microbiology, 2016)

Allogeneic adipose-derived stem cells promote survival of fat grafts in immunocompetent diabetic rats - Jun Zhang; Xiaozhi Bai; Bin Zhao; Yunchuan Wang; Linlin Su; Peng Chang; Xujie Wang; Shichao Han; Jianxin Gao; Xiaolong Hu; Dahai Hu; Xiaoyan Liu (Cell and Tissue Research, 2016)

Distribution and linkage disequilibrium analysis of polymorphisms of GH1 gene in different populations of pigs associated with body size - YUNYUN CHENG; SONGCAI LIU; DAN SU; CHAO LU; XIN ZHANG; QINGYAN WU; SIMING LI; HAOYU FU; HAO YU; LINLIN HAO (Journal of Genetics, 2016)

MRP1 knockdown down-regulates the deposition of collagen and leads to a reduced hypertrophic scar fibrosis - Yan Li; Longlong Yang; Zhao Zheng; Jihong Shi; Xue Wu; Hao Guan; Yanhui Jia; Ke Tao; Hongtao Wang; Shichao Han; Jianxin Gao; Bin Zhao; et al. (Journal of Molecular Histology, 2015)

An Emerging Water Contaminant, Semicarbazide, Exerts an Anti-estrogenic Effect in Zebrafish (Danio rerio) - Su Gao; Wei Wang; Hua Tian; Xiaona Zhang; Linlin Guo; Shaoguo Ru (Bulletin of Environmental Contamination and Toxicology, 2014)

‘Out‐of‐Africa’ dispersal of tropical floras during the Miocene climatic optimum: evidence from Uvaria (Annonaceae) - Linlin Zhou; Yvonne C. F. Su; Daniel C. Thomas; Richard M. K. Saunders (Journal of Biogeography, 2012)
Aim African–Asian disjunctions are common in palaeotropical taxa, and are typically explained by reference to three competing hypotheses: (1) ‘rafting’ on the Indian tectonic plate, enabling Africa‐to‐Asia dispersal; (2) migration via Eocene boreotropical forests; and (3) transoceanic long‐distance dispersal. These hypotheses are tested using Uvaria (Annonaceae), which is distributed in tropical regions of Africa, Asia and Australasia. Recent phylogenetic reconstructions of the genus show a clear correlation with geographical provenance, indicating a probable origin in Africa and subsequent dispersal to Asia and then Australasia. Ancestral areas and migration routes are inferred and compared with estimates of divergence times in order to distinguish between the prevailing dispersal hypotheses. Location Palaeotropics. Methods Divergence times in Uvaria are estimated by analysing the sequences of four DNA regions ( mat K, psb A– trn H spacer, rbc L and trn L–F) from 59 Uvaria species and 77 outgroup species, using a Bayesian uncorrelated lognormal (UCLD) relaxed molecular clock. The ancestral area of Uvaria and subsequent dispersal routes are inferred using statistical dispersal–vicariance analysis ( s‐diva ). Results Uvaria is estimated to have originated in continental Africa 31.6 Ma [95% highest posterior density (HPD): 38.4–25.1 Ma] between the Middle Eocene and Late Oligocene. Two main migration events during the Miocene are identified: dispersal into Madagascar around 17.0 Ma (95% HPD: 22.3–12.3 Ma); and dispersal into Asia between 21.4 Ma (95% HPD: 26.7–16.7 Ma) and 16.1 Ma (95% HPD: 20.1–12.1 Ma). Main conclusions Uvaria fruits are widely reported to be consumed by primates, and are therefore unlikely candidates for successful long‐distance transoceanic dispersal. The other biogeographical hypotheses, involving rafting on the Indian tectonic plate, and dispersal via the European boreotropical forests associated with the Eocene thermal maximum, can be discounted due to incongruence with the divergence time estimates. An alternative scenario is suggested, involving dispersal across Arabia and central Asia via the tropical forests that developed during the late Middle Miocene thermal maximum (17–15 Ma), associated with the ‘out‐of‐Africa’ dispersal of primates. The probable route and mechanism of overland dispersal between Africa and Asia for tropical plant groups during the Miocene climatic optimum are clarified based on the Uvaria data.

Fibronectin and asialoglyprotein receptor mediate hepatitis B surface antigen binding to the cell surface - Jing Yang; Feng Wang; Linlin Tian; Jing Su; Xiangqian Zhu; Li Lin; Xiaoran Ding; Xuejun Wang; Shengqi Wang (Archives of Virology, 2010)